Fuel for Conflict or Balm for Peace? Assessing the Effects of Hydrocarbons on Peace Efforts in Algeria - Miriam Shabafrouz (German Institute of Global and Area Studies (GIGA), 2010)
This paper explores the use of hydrocarbon revenues in post-conflict Algeria. While the bloody years of the 1990s now seem to be over, recurring terror attacks and the ongoing state of emergency leave room for doubt that a situation of stable peace has been achieved yet. It is therefore necessary to evaluate the effectiveness of post-conflict peace-building efforts in Algeria and identify ways of improving these measures. The resources, which are mainly controlled by the central state, can have positive and negative effects on the political economy: they can enhance growth and possibilities for the distribution of wealth, but the dependency on them makes the whole economy vulnerable to crises. Analysing the economic (and other) causes of the outbreak of the intra-state war in 1992 and the reasons for its escalation and its fading out can be revealing when assessing the extent to which critical conditions have or have not been addressed by recent and current peace-building efforts. The author's analysis reveals that the measures taken by the government - such as implementing a programme of national reconciliation, the stimulation of certain sectors of the economy and the resolute reduction of foreign debt - all aim at stabilization and have all been driven by hydrocarbon income to a large extent. However, the recent rise and sudden drop in the price of oil and gas have both had an effect on the scope of these measures and reveal their limits. Moreover, some of the critical causes of the civil war such as the unfair distribution of revenue, the lack of political participation and destabilizing demographic changes still persist and have largely remained unaddressed. One of the author's concluding assumptions therefore is that it is very likely that the use of resource revenues for conflict prevention and peace-building will only lead to sustainable results when embedded in full-fledged reforms of Algeria's entire economic and political system. – – Dieser Aufsatz untersucht die Verwendung von Erdöl- und Erdgaserlösen in Algerien seit Ende des Bürgerkrieges. Zwar scheinen die blutigen 1990er Jahre der Geschichte anzugehören, doch wiederkehrende terroristische Anschläge und eine weiter bestehende Notstandsgesetzgebung zeigen, dass bisher noch kein dauerhafter Frieden erreicht wurde. Daher lohnt es sich zu untersuchen, wie wirksam die Friedensbemühungen in Algerien sind und was zu ihrer Verbesserung geleistet werden könnte. Die Ressourcen, die vor allem vom Zentralstaat kontrolliert werden, können sich auf die Volkswirtschaft des Landes sowohl positiv als auch negativ auswirken: sie können Wachstum verstärken und den Wohlstand der Gesellschaft fördern, doch die Abhängigkeit von ihnen macht die gesamte Wirtschaft anfällig für Krisen. Eine Analyse der wirtschaftlichen (und anderer) Ursachen für den Ausbruch und die Eskalation des innerstaatlichen Krieges dient der Einschätzung, ob die derzeitigen Friedensbemühungen seine wichtigsten Triebkräfte ausreichend berücksichtigen. Die Autorin zeigt, dass die Maßnahmen, die von der Regierung umgesetzt werden - wie das Programm zur nationalen Versöhnung, die Stimulierung zentraler Wirtschaftssektoren und die Rückzahlung der Auslandsschulden - alle die Stabilisierung des Landes anstreben und weitgehend durch Erdöleinnahmen finanziert werden. Entsprechend haben sich sowohl der neuerliche Anstieg der Preise für Erdöl und -gas als auch ihr plötzlicher Fall auf diese Maßnahmen ausgewirkt und damit deren Grenzen offen gelegt. Außerdem sind einige der entscheidenden Gründe für den Bürgerkrieg, wie die ungerechte Einkommensverteilung, geringe politische Partizipationsmöglichkeiten und destabilisierende demographische Dynamiken, bis heute fast unverändert wirksam. Eine wichtige Schlussfolgerung ist daher, dass der Einsatz der Ressourceneinnahmen für Konfliktprävention und Friedensbildung nur dann zu nachhaltigen Ergebnissen führen kann, wenn dies mit umfassenden Reformen des wirtschaftlichen und des politischen Systems in Algerien einhergeht.
Keywords: 300; Algeria; violent conflict; terrorism; peace-building; resource management; socio-economic development; natural resources; oil; gas; Mineralölwirtschaft; Exporterlös; Innere Sicherheit; Sozialer Konflikt; Wirtschaftsförderung; Bürgerkrieg; Algerien